Differential effects of unemployment on depression in people living with HIV/AIDS: a quantile regression approach. Issue 11 (2nd November 2019) - Zeng, Chengbo; Guo, Yan; Hong, Y. Alicia; Gentz, Shelene; Zhang, Jinxin; Zhang, Hanxi; Qiao, Jiaying; Xu, Zhimeng; Cai, Weiping
ABSTRACT: Unemployment is associated with depression in people living with HIV (PLWH). However, few studies have examined the effects of unemployment on PLWH with different levels of depression. The current study explores the plausible differential effects of unemployment on the different percentiles of depression in PLWH employing a quantile regression (QR) approach, based on a recent survey of 411 PLWH in China. Among participants, 47.7% had elevated depressive symptoms, and 23.8% were unemployed. The effects of unemployment on depression were statistically significant with a trend of initial increase followed by a decline at the quantile levels of 0.51–0.90 of depression. The maximum effect of unemployment status on depression was statistically significant at the 70th and 75th percentiles of depression (coefficient = 7.0, p < .01). Tailored strategies and interventions should be implemented to address the differential needs of PLWH with various levels of depressive symptoms.